PENGGUNAAN HIBAH BERSYARAT (BERTA'LIQ) DALAM MASALAH PEMBAHAGIAN MANFAAT TAKAFUL: ANALISIS HUKUM: The Application of Conditional Hibah in Takaful Benefit Distribution: A Juristic Analysis - Ahmad, Mohd Kamil; Borhan, Joni Tamkin (Jurnal Syariah, 2017)
This study seeks to shed light on the issue of conditional hibah, which has been adopted in the Islamic Financial Services Act 2013 (IFSA 2013) and resolved by the Syariah Advisory Council of Bank Negara Malaysia, pertaining to the payment of takaful benefits upon the death of a takaful participant. However, both IFSA 2013 and the resolution by SAC Bank Negara do not differentiate between portions of takaful benefit taken from Participant’s Investment Fund and their Tabarruʻ Fund which may lead to the understanding that both portions may be given as hibah contingent on death. To understand the true nature of conditional hibah and to ascertain the Shariah ruling for both portions constituting the takaful benefit, this study depends largely on literature research where classical and modern texts are referred to. This study preliminarily concludes that a conditional hibah turns into waṣiyyah and the general rulings shall apply, for a person is only allowed to spend one third of his property on succession; as for the remaining two thirds, the rights pertaining to its governance falls absolutely under Allah’s. Therefore, it is necessary to differentiate between rulings for money withdrawn from the Participant’s Investment Fund and the money generated from the commitment of the Tabarruʻ Fund towards the deceased, in which it is his or her right to proceed with the claim. Hence, the first portion of money cannot be made as conditional hibah on death because it turns into waṣiyyah. However, for the other portion; making a conditional hibah of this benefit post-mortem of the insured participant is perhaps allowed because the deceased had not assigned a new owner for his property; it is as if he stipulated upon the takaful fund to pay the benefit to the proposed beneficiary.